The inevitability of change in Chinese and Indian automakers' low cost productive models - Martin Krzywdzinski; Grzegorz Lechowski; Ulrich Jürgens (La nouvelle revue du travail, 2018)
In emerging economies, social change and fast growth have created new automotive markets and a demand for relatively inexpensive, “modern-enough” cars. Up-and-coming local manufacturers and established companies from the Triad countries are competing for dominance in these vast market segments. The paper examines the productive models developed in this context by two indigenous carmakers, one from China (Geely) and the other from India (Mahindra & Mahindra). A variety of tensions are revealed within the two models, relating in particular to labour policies. Both models seek to combine low wages and a reliance on low-cost supply chains with simplified product architectures. Their stability is fragile, however, with one solution involving employee upskilling to increase productive system efficiency. – – En las economías emergentes, el cambio social y el rápido crecimiento han dado origen a nuevos mercados de automóviles, y a una demanda de automóviles relativamente poco caros y bastante modernos. Los fabricantes locales y las empresas extranjeras están en competencia para dominar esos vastos segmentos del mercado. El artículo se enfoca en los modelos productivos desarrollados en este contexto por dos fabricantes de automóviles nativos, uno de China y otro de India. El análisis revela diversas tensiones en el seno de estos modelos, en particular en torno a las políticas de mano de obra. Los dos modelos buscan combinar salarios bajos y cadena de suministro a bajos costos, con arquitecturas de producto simplificadas. Sin embargo, su estabilidad es muy relativa; una de las soluciones pasa por la cualificación de los asalariados para mejorar la eficacia de los sistemas productivos.
Keywords: 330